การผลิตเนยงาดำ Sesamum indicum Linn. - ศุภมาศ กลิ่นขจร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this research is to study procedure of black sesame butter production in various conditions--roasting, grinding, adjusting the taste and choosing the appropriated stabilizer for the product. Temperature and time of roasting were varied into 160, 180, 200 ℃ and 10, 15 , 20 minutes. Then sensory evaluation was studied. The result showed that roasted black sesame at 180 ℃ for 10 minutes, which had 0.52 mg/Kg of TBA value; 4.62% of weight loss and 82.29% of unsaturated fatty acid--35.49% of Oleic acid, 46.67% of Linoleic acid and 0.33% of Linolenic acid, obtained the most overall acceptance score. Afterward grinding black sesame by peanut butter grinder (Oldetyme model: PN-1) was investigated. Grinding was varied into 2, 4, 6, 8 and 10 times. When sensory evaluation was tested, it was found that acceptance scores in term of fineness and spreadability were not different from ideal preference (p˃0.05). Besides, it had got the most acceptance scores. As a result, the researcher selected the eighth grinding, which had 41,280 cPs of viscosity; 10.18 g of force in compression; 0.12 mm/s of spreadability. After that, The taste of sesame butter was adjusted by varying the level of sugar into 22, 24, 26, 28 and 30%(w/w). The result showed that the level of sugar at 26%(w/w) got black sesame butter which had 61,000 cPs of viscosity, 11.06 g of force in compression, 0.09 mm/s of spreadability. When sensory evaluation was tested, it was found that the level of sugar at 26%(w/w) has acceptance sores in term of sweetness and bitterness which are not different from ideal (p˃0.05) and the most acceptance scores. Three stabilizers, using to prevent all separation, were Lecithin (LEC), Distilled Monoglyceride(DMG), Grindsted™ Triglyceride(TG). The concentration was varied by 0.2, 0.4, 0.6, 0.8 and 1.0%)(w/w) . Sensory evaluation was tested. It was found that black sesame butter mixed with 0.2 and 0.4%(w/w)of LEC obtained the same highest overall acceptance score comparing to other concentration. Regarding 0.2%(w/w) of DMG and TG had the highest overall acceptance score. However, the study of all separation at the temperature of 45 and 55 ℃ for 4 weeks, it was found that after 2 weeks black sesame butter added by 0.4%(w/w) of LEC could prevent oil separation better than that added by 0.2%(w/w) of LEC. When sensory evaluation of black sesame butter added by 0.4%(w/w) of LEC and 0.2%(w/w) of DMG and TG was tested. The sensory results revealed that black sesame butter added by 0.4%(w/w) if LEC which had 64,160 cPs of viscosity, 11.82 g of force in compression and 0.08 mm/s of spreadability had the most overall acceptance score.